An integrated pre-clerkship curriculum to build cognitive medical schema: It’s not just about the content - LeClair, Renée J.; Cleveland, Jennifer L.; Eden, Kristin; Binks, Andrew P. (Frontiers in Physiology, 2023)
Both physiology and pathophysiology are essential disciplines in health professional educations however, clinicians do not use this knowledge in isolation. Instead, physicians use inter-disciplinary concepts embedded within integrated cognitive schema (illness scripts) established through experience/knowledge that manifest as expert-level thinking. Our goal was to develop a pre-clerkship curriculum devoid of disciplinary boundaries (akin to the physician’s illness script) and enhance learners’ clerkship and early clinical performance. As well as developing curricular content, the model considered non-content design elements such as learner characteristics and values, faculty and resources and the impact of curricular and pedagogical changes. The goals of the trans-disciplinary integration were to develop deep learning behaviors through, 1) developing of integrated, cognitive schema to support the transition to expert-level thinking, 2) authentic, contextualization to promote knowledge transfer to the clinical realm 3) allowing autonomous, independent learning, and 4) harnessing the benefits of social learning. The final curricular model was a case-based approach with independent learning of basic concepts, differential diagnosis & illness scripting writing, and concept mapping. Small-group classroom sessions were team-taught with basic scientists and physicians facilitating learners’ self-reflection and development of clinical reasoning. Specifications grading was used to assess the products (written illness scripts and concept maps) as well as process (group dynamics) while allowing a greater degree of learner autonomy. Although the model we adopted could be transferred to other program settings, we suggest it is critical to consider both content and non-content elements that are specific to the environment and learner.